Enhanced osseointegration of dental implants with reduced graphene oxide coating - Yong Cheol Shin; Ji-Hyeon Bae; Jong Ho Lee; Iruthayapandi Selestin Raja; Moon Sung Kang; Bongju Kim; Suck Won Hong; Jung-Bo Huh; Dong-Wook Han (Biomaterials Research, 2022)
Abstract Background The implants of pure titanium (Ti) and its alloys can lead to implant failure because of their poor interaction with bone-associated cells during bone regeneration. Surface modification over implants has achieved successful implants for enhanced osseointegration. Herein, we report a robust strategy to implement bioactive surface modification for implant interface enabled by the combinatorial system of reduced graphene oxide (rGO)-coated sandblasted, large-grit, and acid-etched (SLA) Ti to impart benefits to the implant. Methods We prepared SLA Ti (ST) implants with different surface modifications [i.e., rGO and recombinant human bone morphogenetic protein-2 (rhBMP-2)] and investigated their dental tissue regenerating ability in animal models. We performed comparative studies in surface property, in vitro cellular behaviors, and in vivo osseointegration activity among different groups, including ST (control), rhBMP-2-immobilized ST (BI-ST), rhBMP-2-treated ST (BT-ST), and rGO-coated ST (R-ST). Results Spectroscopic, diffractometric, and microscopic analyses confirmed that rGO was coated well around the surfaces of Ti discs (for cell study) and implant fixtures (for animal study). Furthermore, in vitro and in vivo studies revealed that the R-ST group showed significantly better effects in cell attachment and proliferation, alkaline phosphatase activity, matrix mineralization, expression of osteogenesis-related genes and protein, and osseointegration than the control (ST), BI-ST, and BT-ST groups. Conclusion Hence, we suggest that the rGO-coated Ti can be a promising candidate for the application to dental or even orthopedic implants due to its ability to accelerate the healing rate with the high potential of osseointegration.